Quantitative trait locus dissection in congenic strains of the Goto-Kakizaki rat identifies a region conserved with diabetes loci in human chromosome 1q. - Wallace, K; Wallis, R; Collins, S; Argoud, K; Kaisaki, P; Ktorza, A; Woon, P; Bihoreau, M; Gauguier, D (2004)
Genetic studies in human populations and rodent models have identified regions of human chromosome 1q21-25 and rat chromosome 2 showing evidence of significant and replicated linkage to diabetes-related phenotypes. To investigate the relationship between the human and rat diabetes loci, we fine mapped the rat locus Nidd/gk2 linked to hyperinsulinemia in an F2 cross derived from the diabetic (type 2) Goto-Kakizaki (GK) rat and the Brown Norway (BN) control rat, and carried out its genetic and pathophysiological characterization in BN.GK congenic strains. Evidence of glucose intolerance and enhanced insulin secretion in a congenic strain allowed us to localize the underlying diabetes gene(s) in a rat chromosomal interval of approximately 3-6 cM conserved with an 11-Mb region of human 1q21-23. Positional diabetes candidate genes were tested for transcriptional changes between congenics and controls and sequence variations in a panel of inbred rat strains. Congenic strains of the GK rats represent powerful novel models for accurately defining the pathophysiological impact of diabetes gene(s) at the locus Nidd/gk2 and improving functional annotations of diabetes candidates in human 1q21-23.